Reproductive medicine: infertility in Yemen, causes, diagnosis and outcome of assisted reproductive treatment - Allow, Ahmed Kaid Naji; Al-Kubaisi, Muna Khaleel Dheyab; M., Bracamonte; Abdulrazzaq, Saad Mohammed; Al-Muhia, Ibrahim (2013)

(untitled)
Reproductive medicine: is a branch of medicine that deals with prevention, diagnosis and management of reproductive problems; goals include improving or maintaining normal reproductive health and allowing people to have children at a time of their choosing. The objectives of the present prospective study was to review the infertility in Yemen as a part of reproductive medicine and to study the causes of male and female infertility as well as survey the outcome of assisted reproductive treatments. Subjects and Methods: Two thousand sex hundred and twenty two infertile couples (attending Allow IVF Center Sana’a Yemen) had been involved in the present study in the period from September 2007 to September 2011. A total of 1571 cycles were monitored according to the type of protocol and kind of assisted reproductive techniques which will use for the appropriate couple. Three different protocols had been used and it includes the following protocols: 1-clomip hine citrate; 2- tamoxiphine; and 3- administration of gonadotrophin injections of highly purified folliculo-stimulating hormone (FSH-HP). Four ART which includes: Intrauterine insemination-IUI; IVF+ET; ICSI+ET; and ovulation induction by FSH-HP plus or without programming intercourse (PI). Results The present study showed that 65.52% (1718/2622) of the couples have primary infertility, Fig 1. Seventy three per cent of infertile couples had duration of infertility less than or equal to 5 years (1902/2622), 19% have >5 to 10 years duration (5 02/2622) and only 8% of the couples had duration of infertility more than 10 years (208/2622), Fig 2. Approximately, (37.45%) (982/2622) of couples suffering from male factor of infertility and 26.62% (698/2622) had suffered from female factor of infertility, Fig 3. The major causes of male infertility is asthenospermia and seminal fluid infection plus sperm agglutination (25.15% and 17.52%, respectively) and low volume of semen (169/982 ; 17.21%), table 1. The major causes of female infertility had been documented as hyperprolactinemia (40.69%), polycystic ovarian syndrome (28%) and anovulation with luteal phase deficiency (22.49%), table 2. The higher pregnancy , live birth rates had been recorded in the protocol 3 (gonadotrophin injection) versus protocol 2 and 1 respectively. Conclusion The present study concluded that the common causes of infertility in Yemen are associated with chewing Qat and an increase in the percentage of polycystic ovarian syndrome among Yemeni infertile women is might be need to further investigation and follow up of these infertile women.